The writing in the treatises of Baltasar Gracián - Egido, Aurora (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
The voice and Ihe written word are the two fundamental vectors of Baltasar Gracián’s work. This paper is concerned with the second of these as found in his treatises and from which are derived many features which the written word is and symbolizes in El Criticón. Spelling and Typography, page and book are all one and the same thing in the ethics and aesthetics of the jesuit who, like Marcial, was concerned with the physical act of writing. Anticipating the principles of modern grammatology, Gracián blends form and substance to the point of producing a complex mystery which the reader will have to resolve in order to understand and live better.